2000
DOI: 10.1074/jbc.275.12.9043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caspase-3-mediated Poly(ADP-ribose) Polymerase (PARP) Apoptotic Cleavage by Human PARP Autoantibodies and Effect on Cells Undergoing Apoptosis

Abstract: Autoantibodies directed to nuclear antigens are serological hallmarks of autoimmune rheumatic diseases such as systemic lupus erythematosus. Although much more is known about the molecular identity and functions of targeted self-antigens, with few exceptions, evidence that autoantibodies to these targets have a particular function and contribute directly to the pathological process is lacking. Here we show that human autoantibodies reacting with the zinc fingers of poly(ADP-ribose) polymerase involved in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 36 publications
5
75
0
Order By: Relevance
“…Active caspase-8 also causes the release of mitochondrial cytochrome c (Li et al, 1998;Luo et al, 1998) thereby linking the two pathways. After activation, both caspase-8 and caspase-9 activate caspase-3, which in turn cleaves and activates other caspases and many cellular proteins including fodrin, protein kinase C d (PKC d), poly (ADP-ribose) polymerase (PARP), gelsolin, DNA fragmentation factor-45 (DFF45) (Decker et al, 2000;Kunstle et al, 1997;Nicholson and Thornberry, 1997;Wolf and Green, 1999), and Sp1 (Piedrafita and Pfahl, 1997). While proteolysis of these and other caspase substrates induces the hallmark of apoptotic cell death, recent reports have also provided evidence for caspaseindependent apoptosis (Borner and Monney, 1999;Johnson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Active caspase-8 also causes the release of mitochondrial cytochrome c (Li et al, 1998;Luo et al, 1998) thereby linking the two pathways. After activation, both caspase-8 and caspase-9 activate caspase-3, which in turn cleaves and activates other caspases and many cellular proteins including fodrin, protein kinase C d (PKC d), poly (ADP-ribose) polymerase (PARP), gelsolin, DNA fragmentation factor-45 (DFF45) (Decker et al, 2000;Kunstle et al, 1997;Nicholson and Thornberry, 1997;Wolf and Green, 1999), and Sp1 (Piedrafita and Pfahl, 1997). While proteolysis of these and other caspase substrates induces the hallmark of apoptotic cell death, recent reports have also provided evidence for caspaseindependent apoptosis (Borner and Monney, 1999;Johnson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Among the proteins cleaved by caspase-3, PARP is considered relevant for its role in DNA repair and as a marker for caspase activity. 34,35 In previous studies, we suggested that the ERa-dependent PI3K pathway could mediate apoptosis induction by RES in MCF-7 cells. In the present work, we analyzed how RES interferes with downstream signaling in the PI3K pathway.…”
mentioning
confidence: 97%
“…32,33 Among the proteins cleaved by caspase-3, PARP is considered relevant for its role in DNA repair and as a marker for caspase activity. 34,35 Grant sponsor: Fondo Europeo de Desarrollo Regional-Comision Interministerial de Ciencia y Técnologia (FEDER-CICYT); Grant number: 1FD97-0934; Grant sponsor: Junta de Extremadura; Grant number: 2PR01A092.* Abbreviations: Cyt c, cytochrome c; DHDCFDA, 5(and 6)-carboxy-2 0 ,7 0 -dihydrodichlorofluorescein diacetate; DC(m), mitochondrial membrane potential; DTT, dithiothreitol; EMSA, electrophoretic mobility shift assay; ERa, estrogen receptor-a; GSK-3, glycogen synthase kinase-3; I-kB, NF-kB inhibitor; IKK, I-kB-dependent kinase; MMP, matrix metalloproteinase; NF-kB, nuclear factor-kB; NO, nitric oxide; PARP, poly (ADP-ribose) polymerase; PI3K, phosphoinositide 3-kinase; PKB/AKT, protein kinase B/AKT; RES, resveratrol; ROS, reactive oxygen species; TRAIL, tumor necrosis factor-a-related apoptosis-inducing ligand. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment with 20 mg/ml b 2 m for 48 h did not induce cleavage of this enzyme to its active 35 and 37 kDa forms in HL-60 cells and its drug resistant variants (Figure 10b). Poly (ADP-ribose) polymerase (PARP) is a 116 kDa nuclear enzyme that binds DNA strand breaks produced by various genotoxic agents, and it is implicated in conserving the integrity of the genome (Oliver et al, 1998;Decker et al, 2000). This enzyme has therefore been shown as a caspase substrate, and cleavage of PARP from its 116 kDa to an 85 kDa form can be detected in caspase-dependent apoptosis induced by various stimuli (Nicholson and Thornberry, 1997;Decker et al, 2000).…”
Section: Mechanism Of B 2 M-induced Apoptosismentioning
confidence: 99%